Προαγωγή της σεξουαλικής υγείας των εφήβων: παρεμβάσεις στοχευμένες στη μείωση των σεξουαλικώς μεταδιδόμενων νοσημάτων. Μια συστηματική ανασκόπησης - Κατσουρή, Ελένη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Sexually transmitted infections are always a top priority among health professionals as well as top of the list of World Health Organization among the subjects that need immediate intervention. Most interventions are targeted to adolescents aiming to reduce or eliminate risk behaviours related to increased chances of infection from HIV/ STI. Most interventions fail to coop due to the absence of an integrated approach around the subject. Purpose: To examine the effectiveness of interventions aiming towards the reduction of sexually transmitted infections (STI), among adolescents. Methods: For this systematic review we examined interventions that aimed at STI reduction. To retrieve the related articles, the databases PUBMED, COCHRANE, GOOGLE SCHOLAR, EMBASE, and WEB OF KNOWLEDGE were used along with international organizations’ websites. The chosen articles were all in English. The filtering process left 34 027 published articles, we performed a second search on this group and ended up with 7 090 articles, from them we finally used 11 articles that fulfilled our criteria. The articles were published from 1995-2010. A detailed reading and research of the 11 articles that were decided to be used was conducted. The terms sexually transmitted infections and adolescents were recognized in the selected articles. Results: This systematic review revealed that most health interventions aimed at STI prevention and reduction among adolescents can improve sexual health and strengthen knowledge and attitudes of teenagers. But their influence on sexual behavior remains limited. Conclusion: There is a greater need for further research in the field of health interventions aimed at STI’s and their effectiveness towards sexual health of adolescents.
Keywords: Sexually Transmitted Diseases; AIDS (Disease)